To the publick. New-York, October 5, 1774 : By Mr. Rivere, who left Boston on Friday last ... we have certain intelligence that the carpenters and masons who had inadvertently undertaken to erect barracks for the soldiers in that town, upon being informed that it was contrary to the sentiments of their countrymen, unanimously broke up . (Printed by John Holt, near the coffee House., 1774)
Encouraging the mechanics of New York not to participate in the construction of barracks for the British soldiery.